Factors influencing people's continuous watching intention and consumption intention in live streaming: Evidence from China. Issue 1 (4th July 2019) - Hou, Fangfang; Guan, Zhengzhi; Li, Boying; Chong, Alain Yee Loong
Abstract : Purpose: The purpose of this paper is to investigate what factors can affect people's continuous watching and consumption intentions in live streaming. Design/methodology/approach: This research conducted a mixed-methods study. The semi-structured interview was deployed to develop a research model and a live streaming typology. A survey was then used for quantitative assessment of the research model. Survey data were analyzed using partial least squares-structural equation modeling. Findings: The results suggest that sex and humor appeals, social status display and interactivity play considerable roles in the viewer's behavioral intentions in live streaming and their effects vary across different live streaming types. Research limitations/implications: This research is conducted in the Chinese context. Future research can test the research model in other cultural contexts. This study can also be extended by incorporating the roles of viewer gender and price sensitivity in the future. Practical implications: This study provides managerial insights into how live streaming platforms and streamers can improve their popularity and profitability. Originality/value: The paper introduces a novel form of social media and a new business model. It illustrates what will affect people's behavioral intentions in such a new context.